Da ouvinte sem voz à mercadoria corporificada : imagem, mulher e feminino em Walter Benjamin - Paula Coelho Barroso Magalhães (2024)
This work sets out to investigate erotic-feminine images throughout the transformations of Walter Benjamin's thought. It is clear that the image occupies an important and sui generis status in his work, but not so much how it is associated with the figures of eroticism, women and the feminine. How does Benjamin see women? How do they fit into his thinking as a whole and, moreover, how do they transform his thinking, once this possibility is assumed? In the first chapter, we address the problem of the image in general, which is in line with the idea of untimely, anachronistic temporality. In the second, we look at the erotic-feminine images of women in relation to language and theology, based on the dialog explored by Benjamin between Sappho and her friends. In the third, we look at these images in relation to the main Marxian categories, especially commodity and labor, starting with the "conquest" of virility by women in modern times. The lesbian and the prostitute are constant central figures throughout the author's texts, but they are approached from different points of view according to their phases of thought, a change that marks the distinction between the last two chapters of this work. These images oscillate between hell and utopia: they are voiceless listeners who lead the speaker into the abyss of their own history, and they are heroines of modernity who redeem the whole of humanity. In the end, we conclude that the dialectic present in the way Benjamin thinks about women and the feminine is reflected in speech and listening, past and present, street and home, commodity and human. Therefore, on the one hand, there are reifications and, on the other, prodigious ambiguities on this subject.